Fatty acid synthase 2 knockdown alters the energy allocation strategy between immunity and reproduction during infection by Micrococcus luteus in Locusta migratoria - Ma, Tingting; Tang, Ya; Jin, Yi; Xu, Jiaying; Zhao, Huazhang; Zhou, Min; Tang, Bin; Wang, Shigui (Pesticide biochemistry and physiology, 2024)
Immunity and reproduction are vital functions for the survival and population maintenance of female insects. However, owing to limited resources, these two functions cannot be fulfilled simultaneously, resulting in an energy tradeoff between them. Notably, the mechanisms underlying this immune-reproductive trade-off, in which energy competition likely plays a central role, remain poorly understood. Fatty acid synthase (FAS), a key gene involved in lipid synthesis and insect energy metabolism, was investigated in this study using Locusta migratoria as the research subject. Bacterial infection and RNA interference (RNAi) technology were used to examine changes in the immunity, fecundity, and energy metabolism patterns of locusts under different treatments. The findings of this study demonstrate that infection with Micrococcus luteus triggers an immune response in locusts, significantly upregulates the expression of defensin 3 (DEF3) and Attacin, and enhances pHenoloxidase (PO) activity. Upon FAS2 silencing, bacterial attack upregulated DEF3 and Attacin expression to a lesser extent, leading to increased lysozyme activity instead of PO. Furthermore, bacterial infection results in a decrease in glycogen and glucose content in the fat body, accompanied by a significant increase in triacylglycerol (TAG) content. However, after FAS2 knockdown, both the lipid and carbohydrate contents were significantly reduced in the fat body. Compared with bacterial infection alone, low FAS2 expression further exacerbated fecundity impairment in locusts. The expression levels of vitellogenin A (VgA) and vitellogenin B (VgB) were significantly low, with severe ovarian atrophy observed. Notably, the ovarian weight was only 21 % compared to that of the control group. Moreover, females exhibited minimal egg-laying behavior. In summary, our findings suggest that following FAS2 gene silencing, there is a greater inclination toward immune stimulation energy activation in locusts, whereas reproductive investment is reduced. The outcomes of this study will contribute to the further exploration of the molecular mechanisms underlying the trade-off between immune and reproductive energy in locusts. [Display omitted] •M. luteus infection reduces the fecundity of locusts.•LmFAS2 plays an important role in lipid synthesis and reproduction.•dsFAS2 + M. luteus infection seriously impaired the fecundity of locusts.